Effect of nickel on the kinematic stability of retained austenite in carburized bearing steels – In-situ neutron diffraction and crystal plasticity modeling of uniaxial tension tests in AISI 8620, 4320 and 3310 steels. (August 2020) - Bedekar, Vikram; Voothaluru, Rohit; Yu, Dunji; Wong, Adriel; Galindo-Nava, Enrique; Gorti, Sarma B.; An, Ke; Hyde, R. Scott
Abstract: The presence of kinematically metastable retained austenite in the microstructure of bearing components can significantly affect the macro and micro-mechanical material response. In the present work, the influence of Ni on the stability of the retained austenite within three different grades of high carbon bearing steel using in-situ neutron diffraction is investigated. For the first time, the results show that presence of Ni increases the stability of the austenite in the elastic regime whereas the transformation rate remains unaffected. Crystal plasticity finite element (CPFE) modeling was used to study the deformation in these three steels and shows that the predominant factor causing the difference in mechanical behavior of these steels is the austenite stability. The elastic and plastic response of the matrix martensite was found to be identical among all specimens while the austenite demonstrates similar elastic behavior but remarkably different stabilities under monotonic loading. Graphical abstract: Image 1 Highlights: Retained austenite was stable in the macro-scale elastic regime for bearing microstructures. Amount of nickel played an influential role in the stability of retained austenite. Lattice strain evolution for martensite and retained austenite occurs in three distinct stages. A hybrid crystal plasticity model captured the lattice strain response of constituent phases.